Assessment of outdoor thermal comfort and wind characteristics at three different locations in Peninsular Malaysia - Hanipah, M. H. (EDP Sciences, 2016)
Urbanization and rapid growth in construction have led to the problems of global warming and urban heat island throughout the world. In order to reduce these problems particularly in hot and humid climatic region, a research on current level of outdoor thermal comfort and wind characteristics based on the local weather conditions around Malaysia should be conducted. This paper reports on the analysis of outdoor thermal comfort level at hottest temperatures and wind characteristics at three locations in Peninsular Malaysia by using hourly climatic data recorded by Malaysian Meteorological Department (MetMalaysia). The level of outdoor thermal comfort was assessed based on the Universal Thermal Climate Index (UTCI). The results showed extreme heat stress conditions have occurred at Alor Setar, Kuantan, and Subang with UTCI values of 51.2°C, 49.7°C, and 49.0°C respectively taking into account only temperature data from the year 2012 to 2014. However, for 20 years data from 1994 to 2014, the calculated UTCI also showed extreme heat stress conditions with their respective values of 49.6°C, 43.8°C, and 49.7°C for Alor Setar, Kuantan, and Subang respectively. Meanwhile, the hourly mean wind speed for three years data at Alor Setar, Kuantan, and Subang, were 1.70m/s, 1.69m/s, and 1.63m/s respectively. The highest mean wind speed of 11.6m/s was observed at Subang, while no wind movement (i.e. 0m/s) was considered to be the lowest hourly wind speed for all three locations. The observed prevailing wind direction for all the three locations was from the north (0°). It can be concluded that Peninsular Malaysia is generally facing extreme heat stress problem due to unfavourable climatic conditions.